1982
DOI: 10.1152/ajpregu.1982.242.3.r220
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and endocrine responses to hypothalamic electrical stimulation in rats

Abstract: The effect of ventromedial (VMN) or basolateral (LHA) hypothalamic electrical stimulation on glucose and hormone production was examined in conscious and anesthetized male rats. Barbiturate treatment alone led to large increases of corticosterone and smaller but significant increases of glucose, insulin, and glucagon. When hypothalamic stimulation was combined with anesthesia, interactions between the hypothalamic sites and the awake-anesthetized conditions were observed. This was most evident with LHA placeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Our findings that Ucn3/TRH axons densely innervate the VMN and constitute almost the entire TRH innervation and the total Ucn3 innervation of this nucleus strongly suggest that Ucn3/TRH neurons are involved in the regulation of feeding, as both TRH and Ucn3 decrease food intake and increase blood glucose levels when injected to the VMN (Suzuki et al,1982; Shen et al,1985; Fekete et al,2007; Li et al,2007). Since the electrical stimulation of the VMN inhibits feeding (Beltt and Keesey,1975; Ruffin and Nicolaidis,1999) and causes hyperglycemia (Dubuc et al,1982), these data indicate that Ucn3/TRH axons exert stimulatory effects on VMN neurons. Reducing food intake probably involves the stimulation of leptin‐sensitive neurons located in the dorsomedial part of the VMN (Elmquist et al,1997,1998), a region that also receives the highest density of Ucn3/TRH axons.…”
Section: Discussionmentioning
confidence: 94%
“…Our findings that Ucn3/TRH axons densely innervate the VMN and constitute almost the entire TRH innervation and the total Ucn3 innervation of this nucleus strongly suggest that Ucn3/TRH neurons are involved in the regulation of feeding, as both TRH and Ucn3 decrease food intake and increase blood glucose levels when injected to the VMN (Suzuki et al,1982; Shen et al,1985; Fekete et al,2007; Li et al,2007). Since the electrical stimulation of the VMN inhibits feeding (Beltt and Keesey,1975; Ruffin and Nicolaidis,1999) and causes hyperglycemia (Dubuc et al,1982), these data indicate that Ucn3/TRH axons exert stimulatory effects on VMN neurons. Reducing food intake probably involves the stimulation of leptin‐sensitive neurons located in the dorsomedial part of the VMN (Elmquist et al,1997,1998), a region that also receives the highest density of Ucn3/TRH axons.…”
Section: Discussionmentioning
confidence: 94%
“…From a teleological perspective, it makes intuitive sense that, when glucose availability is threatened, responses that increase glucose production would be activated (e.g., elevated glucagon and corticosterone levels) in concert with responses that reduce glucose clearance (e.g., inhibition of insulin secretion), and much of the literature indicates that pancreatic beta cells are subject to inhibitory control via the sympathetic nervous system (SNS) (47,48). For example, bilateral VMN lesioning induces hyperinsulinemia (49,50) whereas electrical stimulation of the VMN suppresses glucose-induced insulin secretion (51). Further, the VMN is known to regulate autonomic outflow to the pancreas (52,53), and activation of islet sympathetic nerves during glycopenic stress (54) inhibits insulin secretion via a mechanism involving activation of α2-adrenoreceptors on the beta cell (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Although glucose counterregulation involves multiple brain areas (1), neurons in the hypothalamic ventromedial nucleus (VMN) appear to play an important role. This assertion is based on evidence that 1 ) the VMN is activated during hypoglycemia (7), 2 ) electrical stimulation of the VMN activates CRRs and raises blood glucose levels (8,9), and 3 ) glucose delivery specifically within the VMN blunts CRRs during systemic hypoglycemia (10). Moreover, using an optogenetics approach, we recently demonstrated that activation of the subset of VMN neurons that express steroidogenic factor 1 (VMN SF1 neurons) activates CRRs and thereby raises blood glucose levels, whereas their inhibition blocks recovery from hypoglycemia (11).…”
Section: Introductionmentioning
confidence: 99%